Characteristics of water and droplet size distribution from fluidic sprinklers†. (29th August 2016) - Liu, Junping; Yuan, Shouqi; Darko, Ransford Opoku
Abstract: A new prototype of fluidic sprinkler (PXH) is proposed and its working theory is reported. The hydraulic performance of four different types of sprinkler head (PXH, PY, Toro S 800 and RainBird S 3504) was compared at the same operating pressure. Meanwhile, PXHs with nozzle diameters of 4, 6 and 8 mm were tested to establish a mathematical model of water distribution and droplet diameter. The results show that the PXH produces the longest wetted radius, potentially due to its unique working principles. The PXH exhibits optimal water distribution performance because the air in the nozzle destroys the fluid structure of the water jet. The PXH results in the smallest droplet diameter, which transfers less kinetic energy to the soil. The results from the empirical equations of a distribution model from the PXH were plotted against actual values to obtain regressions, with coefficients of determination ranging from 95.1 to 98.8%. The droplet size model was determined by fitting the experimental results obtained using different operating pressures and nozzle diameters. The model was verified using the experimental results of six cases with different droplet diameters. The average relative error between the predicted and measured droplet diameters was 4.6%. Copyright © 2016 John Wiley & Sons, Ltd.